Microbiological assay for lomefloxacin in coated tablets - Gomes, Greici Cristiani; Salgado, Hérida Regina Nunes [UNESP] (Aoac International, 2006)
The validation of a microbiological assay, applying cylinder plate method for determination of the activity of lomefloxacin in coated tablets is described. Using a strain of Bacillus subtilis ATCC 9372 as the test organism, lomefloxacin was measured in concentrations ranging from 2.0 to 8.0 mu g/mL. The method validation showed that it is linear (r = 0.9999), precise (relative standard deviation 1.15%), and accurate (it measured the added quantities). The excipients did not interfere in the determination. It was concluded that the microbiological assay is satisfactory for quantitation of lomefloxacin in tablets.